Exploring the Influence of Learning Motivation and Socioeconomic Status on College Students’ Learning Outcomes Using Self-Determination Theory - Li, Hao; Peng, Michael Yao-Ping; Yang, Mingyue; Chen, Chun-Chun (Frontiers in Psychology, 2020)
Higher education, which has the function of cultivating human capital, has already become a key focus of developed countries around the world. From ministries of education to higher education institutions, many bodies are dedicated to enhancing student learning outcomes. However, social and educational problems derived from disadvantaged groups have long been hindering the development of individuals and the whole country. This study examines the learning motivations of economically disadvantaged versus non-disadvantaged college students and evaluates the relationship between learning modes and learning outcomes from a self-determination theory (SDT) perspective. In this study, 817 valid questionnaires were collected to compare the two sample groups in terms of learning path. The results show that non-economically disadvantaged students have superior outcomes compared to disadvantaged students in terms of role identity, academic identity, explorative learning, exploitative learning, and cognitive and non-cognitive gains. In regard to path analysis, economically disadvantaged students are significantly superior to non-disadvantaged students in the face of positive influence of academic identity on different learning modes and positive influence of explorative learning on cognitive and non-cognitive gains. Finally, based on the conclusions, this study proposes some suggestions specific to theoretical mode for future study.